2017
DOI: 10.1002/ccd.27033
|View full text |Cite
|
Sign up to set email alerts
|

A first in human evaluation of a novel contrast media saving device

Abstract: The DyeVert System substantially decreases contrast delivered to patients during diagnostic or interventional coronary procedures while maintaining adequate image quality. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…The DyeVert™ Contrast Reduction System (DyeVert System, Osprey Medical) was cleared by the Food and Drug Administration (FDA) for the purpose of reducing CMV delivered to patients during angiography procedures. Early experience with this device from European centers has demonstrated clinically and statistically meaningful reductions in CM delivered to the patient . We report the results of a single‐arm, observational study evaluating the safety and efficacy of the latest version of the product, DyeVert Plus System, which includes continuous CM threshold monitoring, across multiple participating sites.…”
Section: Introductionmentioning
confidence: 99%
“…The DyeVert™ Contrast Reduction System (DyeVert System, Osprey Medical) was cleared by the Food and Drug Administration (FDA) for the purpose of reducing CMV delivered to patients during angiography procedures. Early experience with this device from European centers has demonstrated clinically and statistically meaningful reductions in CM delivered to the patient . We report the results of a single‐arm, observational study evaluating the safety and efficacy of the latest version of the product, DyeVert Plus System, which includes continuous CM threshold monitoring, across multiple participating sites.…”
Section: Introductionmentioning
confidence: 99%
“…The DyeVert Plus XT System in combination with manual CM injection techniques has been introduced to perform real-time CM dose monitoring and significantly and consistently reduce CM volumes [7,15,20,21]. Corcione et al used the DyeVert Plus for coronary and peripheral applications and found a reduction in applied CM of 41.8 ± 7.3% (95% CI, 37.5 to 46.4; p < 0.05) [20].…”
Section: Discussionmentioning
confidence: 99%
“…This field has been further extended by the pioneering work of Ali and colleagues who have reported on a series of patients on whom they were able to perform PCI without using any contrast media whatsoever . More recently, studies of the Dyevert system (Osprey Medical Inc., Minnetonka, MN) have demonstrated clinically and statistically significant reductions in the volume of contrast media administered during coronary angiography and/or interventions .…”
Section: Discussionmentioning
confidence: 99%